Model keterkaitan resource–capability–market forces terhadap pembentukan strategi bersaing dan hasil kinerja perusahaan - Triyono Arief Wahyudi (Jurnal Riset Manajemen dan Bisnis, 2023)
This study analyzes the influence of company resources, capabilities, customers, and competitors on competitive strategy and firm performance. A quantitative approach was employed, involving 78 senior employees from service companies in DKI Jakarta. Data were collected through questionnaires and analyzed using multiple regression analysis after validating instrument reliability and classical assumptions. The findings reveal that while company resources and customer-related factors do not significantly affect competitive strategy, capabilities and competitor-related factors exert significant positive influences. Furthermore, competitive strategy significantly enhances company performance. These results highlight that capabilities and competitive awareness are more critical than resource ownership alone in shaping effective strategies. Practically, service firms should prioritize capability development—such as employee training and innovation processes—and strengthen competitor monitoring to improve strategic responsiveness. Policymakers and industry associations may also support sector competitiveness through capability-building programs and knowledge-sharing platforms